An organometallic half-sandwich supramolecular complex {K(18-Crown-6)(ηn-C6H5B(C6H5)3)} (n = 1–6) exhibiting a reversible breaking-symmetry phase transition and switchable dielectric behaviour. Issue 47 (12th November 2018) - Yuan, Guo-Jun; Shao, Dong-Sheng; Yao, Zhi-Yuan; Liu, Wen-Long; Ren, Xiao-Ming
Abstract : An organometallic supramolecular crystal of {K(18-crown-6)(η n -C6 H5 B(C6 H5 )3 )} ( n = 1–6) has a half-sandwich structure and exhibits a reversible breaking-symmetry phase transition and switchable dielectric behavior. Abstract : A supramolecular crystal, built from a 1 : 1 molar ratio of potassium tetraphenylboron (KBPh4 ) with 1, 4, 7, 10, 13, 16-hexaoxacyclooctadecane (18-Crown-6), contains an organometallic half-sandwich superstructure unit {K(18-Crown-6)(η n -C6 H5 B(C6 H5 )3 )} (1 with n = 1–6), and shows a reversible phase transition at ∼211 K. The analysis of crystal structures at 173 K in the low-temperature phase, and 293 and 423 K in the high-temperature phase revealed that the breaking-symmetry phase transition is associated with the order–disorder transformation of [K(18-Crown-6)] + and the change of the coordination mode of the phenyl ring to K + . A dielectric anomaly appears at ca. 212 K and dielectric relaxation occurs above 375 K in1 . The dielectric and thermal anomaly temperatures are close to each other, and the dielectric relaxation is relevant to the relative displacement of [K(18-Crown-6)] + and the tetraphenylboron anion.